AllanBakes really good cheesecakes : with tips and tricks for successful baking - Allan Albert Teoh (Singapore Marshall Cavendish Cuisine, 2013)
hen Allan first set up his cafe a decade ago, little did he know how fast the accolades would come. His strawberry cheesecake was featured as one of the 50 Yummiest Cakes in Singapore and he was Read more...
Keywords: Cheesecake. Baking. COOKING -- General